INCREASING VOCABULARY MASTERY RELATED TO REQUEST AND COMMAND USING SHORT STORY AT THE SIXTH YEAR STUDENTS OF SD N 1 KLUWAN PENAWANGAN GROBOGAN REGENCY IN 2010/2011 ACADEMIC YEAR - SISWOROWATI, DWI RETNO (2011)
The general objective of this research is to improve the students' vocabulary mastery. While the specific objectives of this research are to describe the implementation of teaching English vocabulary related to request and command using short story at the sixth year students of SD N 1 Kluwan Penawangan and to describe the result of teaching English vocabulary related to request and command using short story. In achieving the objectives of this research, the writer uses Classroom Action Research (CAR). Each cycle of this action research consists of four steps: planning, acting, observing, and reflecting. The research was held in SD N 1 Kluwan consisting of 33 students. In analyzing the data, the writer uses both qualitative and quantitative analysis taken from documentation, observation, and interview. There are two cycles in this action research in which each cycle is conducted in two meetings. The result of research shows that the mean score of pre-test is 49,33 , in post-test I is 64,57 and in post-test II is 82,39. It indicates that the students have an improvement in vocabulary mastery. Through short story with picture, the students became more active and did not easily bore in English class. They could also more easily memorize the English words. Thus, it can be said that teaching English vocabulary using short story technique is successful to improve the students' vocabulary mastery in SD N I Kluwan, Penawangan.